Online Parameters Identification for an IPMSM Based on Extended Kalman Filter - Treebubpha, Khanaphot; Polmai, Sompob; Kittiratsatcha, Supat (My University, 2024)
This paper introduces an online identification of d-q axis apparent inductance in an interior permanent magnet synchronous machines (IPMSM) using extended Kalman filter (EKF). The primary objective is to achieve accurate tracking of apparent inductances, which are nonlinear and varies under different operating conditions. The apparent inductances are crucial for calculating electromagnetic torque. A nonlinear IPMSM model based on finite element analysis (FEA) is employed for simulations. The effectiveness of the proposed approach is demonstrated through MATLAB/Simulink simulations. To verify the efficiency of real-world application, two machines with different conditions were investigated under various operating scenarios, with the results compared to steady state analysis to ensure the accuracy of the proposed estimation method.
Keywords: Extended Kalman filter (EKF); interior permanent magnet synchronous machines (IPMSM); nonlinear model; parameters identification